Displaying the short-term consequences of an unhealthy diet in gain and loss framed messages to encourage the use and success of nutritional warnings to promote healthier food choices in young adults (2024)
The escalating global burden of non-communicable diseases (NCDs) needs effective public health strategies. Front-of-package (FOP) nutrition labeling emerges as a pivotal approach to empower consumers in making informed food choices and combating NCDs. This study explores the impact of short-term gain and loss-framed nutrition messages on attention to FOP warning labels and subsequent food choices among young adults. A between-subjects design with eye tracking methodology was employed, with data from 47 participants. Results indicate that exposure to short-term loss-framed messages led to reduced attention to FOP warning labels while gain-framed messaging had no significant effect on attention. Moreover, no significant differences in food choice were observed among the groups. Findings suggest a possible negative reaction toward loss-framed messages, which triggers visual avoidance as found in tobacco warning labels research. However, further research is necessary to delve into the mechanisms of this avoidance and its behavioral ramifications. Despite limitations in sample size and stimulus perception, this study underscores the need for nuanced approaches in public health messaging to foster healthier dietary behaviors, especially among young adults. Future investigations should delve into the efficacy of short-term framed nutrition messaging and its implications for public policy interventions aimed at promoting healthier eating habits and combating NCDs.